Synthesis and characterization of polypyrrole/Sn-doped TiO2 nanocomposites (NCs) as a protective pigment - Mahmoudian, M.R.; Ebadi, M.; Alias, Y.; Basirun, Wan Jefrey (2011)
We have chemically polymerized pyrrole in the presence of Sn-doped TiO2 nanoparticles (NPs) and TiO2 (NPs) which act as a protective pigment. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) results show a core-shell structure of pigments in which TiO2 and Sn-doped TiO2 NPs have a nucleus effect and caused a homogenous PPy core-shell type morphology leading to coverage of the TiO2 and Sn-doped TiO2 NPs by PPy deposit. The XRD results indicate that the crystalline size of polypyrrole/TiO2 NCs and polypyrrole/Sn-doped TiO2 NCs were approximately 93.46 +/- 0.06 and 23.36 +/- 0.06 nm respectively. The electrochemical impedance spectroscopy (EIS) results show that the performance of polypyrrole/Sn-doped TiO2 NCs is better than polypyrrole/TiO2 NCs. The results indicate that increasing the area of synthesized polypyrrole in the presence of Sn-doped TiO2 NPs can increase its ability to interact with the ions liberated during the corrosion reaction of steel in the presence of NaCl. The UV-vis results show that the band gap of TiO2 NPs increases with doped of Sn in lattice of TiO2. The increase of the band gap of TiO2 with doping of Sn can decrease the charge transfer through the coating. (C) 2011 Elsevier B. V. All rights reserved.